Draft Annual Plan, 1982-83 Volume I Government of Arunachal Pradesh - Planning Commission (Planning Commission, 1982)
The concept of integrated area development based on efficient land and water use with an inner1ir programme of infrastructure development, increasing productivity and provision of social and community services was adopted as the major strategy for the Sixth Five Year Plan 1980-85 of the Union Territory of Arunachal Pradesh.
Government of Arunachal Pradesh, Planning and Development Department